The educational philosophies of Camilo Osias and Pedro T. Orata a comparative analysis - Halili, Adoracion Mamawi
These educators, each in his own time had contributed and worked vigorously towards the development of our country in general. Osias has shown distinctive achievements as (1) a person (2) a professional (3) an educator (4) a politiciam and (5) an agent in promoting social change - more specifically for a dynamic Filipinism. He is always be remembered as a dynamic nationalist and a stout defender of academic freedom and civil liberties.
On the other hand, Orata's influence is far reaching, considering the 1,900 barrio schools now open all over the country, 67 community colleges and some 1,000 pre-school classes. Much has been accomplished towards the direction of community service revealing one of the tests of the effectiveness of the educational program which is the way the program brings about improved ways of living in the community and all over the country.
Keywords: Osias, Camilo -- Philosophy; Orata, Pedro Tamesis -- Philosophy; Education -- Philosophy; Education -- Philippines